1999
DOI: 10.1126/science.286.5440.763
|View full text |Cite
|
Sign up to set email alerts
|

A Triassic Fauna from Madagascar, Including Early Dinosaurs

Abstract: The discovery of a Middle to Late Triassic ( approximately 225 to 230 million years old) terrestrial vertebrate fauna from Madagascar is reported. This fauna documents a temporal interval not well represented by continental vertebrate assemblages elsewhere in the world. It contains two new prosauropod dinosaurs, representing some of the earliest dinosaur occurrences known globally. This assemblage provides information about the poorly understood transition to the dinosaur-dominated faunas of the latest Triassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 8 publications
(4 reference statements)
1
51
0
2
Order By: Relevance
“…For example, Flynn et al (1999) reported two new sauropodomorph dinosaurs from the early Late Triassic of Madagascar.…”
Section: Taxa Often Mistaken As Dinosaursmentioning
confidence: 99%
“…For example, Flynn et al (1999) reported two new sauropodomorph dinosaurs from the early Late Triassic of Madagascar.…”
Section: Taxa Often Mistaken As Dinosaursmentioning
confidence: 99%
“…The analysis resulted in 67 most parsimonious trees (MPTs), each having a length of 127 steps (CI 5 0.520, RI 5 0.712, RC 5 0.370). The strict consensus of these MPTs shows that both Trirachodontinae and Sinognathinae are well supported as monophyletic clades, but the two clades ended with Traversodontidae (see Flynn et al, 1999, for a different definition of the family) as a trichotomy in the strict-consensus tree ( fig. 7A).…”
Section: Descriptionmentioning
confidence: 99%
“…Recently, Flynn et al (1998Flynn et al ( , 1999Flynn et al ( , 2000 reported a rich tetrapod fauna from the base of the 'Isalo II beds' (Makay Formation of Razafimbelo, 1987) in the southern part of the Morondava Basin, southwestern Madagascar, including procolophonids, prosauropod dinosaurs, sphenodontians, dicynodonts, traversodontid cynodonts, 'eosuchians,' and rhynchosaurs. Dicynodonts, procolophonids, traversodontids, and rhynchosaurs occur throughout the mid-late Triassic, whereas sphenodontians and prosauropods in the fauna suggest a Late Triassic age (Lucas, 1998a).…”
Section: Tracing the Ischigualastian Throughout South Pangeamentioning
confidence: 99%
“…Jalil and Knoll, 2002) come from strata that appear coeval with the Ischigualasto Formation. However, Flynn et al (1999Flynn et al ( , 2000 suggest a pre-Ischigualastian age for their Isalo II fauna on the basis of (1) the absence of aetosaurs, (2) the high diversity of traversodontid cynodonts, and (3) the phylogenetic position of the rhynchosaur Isalorhynchus and the traversodontids Dadadon and Menadon.…”
Section: Tracing the Ischigualastian Throughout South Pangeamentioning
confidence: 99%